Hubungan Spiritualitas dengan Kecemasan Perawat dalamMenangani PasienCOVID 19 di RSUD Temanggung - Nurul Fitri Hidayati; Sambodo Sriadi Pinilih; Retna Tri Astuti (Buletin Kesehatan: Publikasi Ilmiah Bidang kesehatan, 2022)
Background: The number of phenomena in covid cases continues to increase from day to day so that health workers as the front line are increasingly stressed due to the increasing workload, worrying about their health, and their families. For health workers, the consequences of this pandemic have caused many physical and psychological impacts, psychological impacts such as anxiety. Good spirituality will have a positive impact on reducing anxiety for nurses who treat patients. Objective: This study aims to determine whether there is a relationship between spirituality and nurse anxiety in dealing with Covid-19 patients at Temanggung Hospital. Methods: Using a quantitative research design with a Cross Sectional approach, using a sample of 90 respondents. The instrument used is a spiritual level questionnaire using the Daily Spiritual Experience Scale (DSES) and an anxiety level questionnaire using a Self Reporting Questionnaire (SRQ 20). The data was processed using the Spearman Rank Statistical Test. Result: there is a significant relationship between spirituality level and nurses' anxiety in dealing with COVID-19 patients at Temanggung Hospital with a value (p = 0.000). Conclusion: Good spirituality will show no anxiety, and bad spirituality will show anxiety. Suggestion: it is hoped that it can improve the professionalism of nurses, especially in improving the spirituality of nurses so that nurses' anxiety in dealing with Covid-19 patients can be minimized.